Exploring Students Learning Strategies in Extensive Reading Activity through Narrative Inquiry - Alfian Alfian; Rubica Himawan Evto; Agriska Agriska; Vanessa Angelica (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2022)
This study focused on students' learning strategies and extensive reading experience, as well as the varied tactics and disparities between them. In this study, the narrative inquiry method was applied. We polled ten active university students from a variety of disciplines and faculties. While conducting the intensive reading tasks, the researchers asked the respondents a few questions and asked them to discuss their experiences. The students were also interviewed over the phone by the researchers. The researchers chose the responders at random, without considering their major, knowledge, or other factors. Based on the findings, we can deduce that each student has similar challenges and employs a similar learning technique. The majority of them use online dictionaries to look up the definitions of new words.